PERAN DEWAN PENGAWAS SYARIAH (DPS) DALAM PENERAPAN SHARIAH COMPLIANCE PADA BAITUL MAAL WA TAMWIL (BMT) DI KOTA PURWOKERTO - Akhmad Faozan (IAIN Purwokerto, 2015)
Abstract: The results of this study indicate that: (1) DPS DPS at BMT-BMT in Purwokerto yet fully run seven role in BMT. They've run four roles that include directing, reviewing, supporting and playing. Three other role includes supervising, marketing, and mediating has not been implemented by the DPS of BMT-BMT in Purwokerto, (2) BMT-BMT in Purwokerto yet fully apply the shariah compliance. Of the six elements contained in the shariah compliance, BMT-BMT only applicate two elements, namely the conduct of halal profit business activities and trustful in paying and managing zakat and sadagah donation. Four other elements that have not been applied, that is, free of usury, gharar, gambling and trustworthy in operation; and (3) Constraints faced by DPS in their role as a watchdog of shariah compliance in BMT-BMT in Purwokerto are: (a) DPS's lacking knowledge about banking operations; and (b) DPS tend to occupied by their original jot. Keywords: Sharia Supervisory Board (DPS), Shariah Compliance, BMT